PENGEMBANGAN TES KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI SISTEM PERSAMAAN LINEAR UNTUK MAHASISWA CALON GURU MATEMATIKA - Amrina Rizta; Luvi Antari (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to develop instrument for measuring mathematical communication skills of student prospective mathematics teacher. Development of this instrument used ADDIE model that has five steps: analyze, design, develop, implement, and evaluate, but in this study only done until the develop step. This instrumen test consists of five items essay test. Validation of this test performed twice that is content validation and empirical validation. The result content validity and emperical validation is all of item valid. After that, to know the reliability, the differentiating power, and the difficulty of item in the instrument conducted trials. The result show that valid items have reliabity coefficient Alpha Cronbach is 0,708, the diffrentiating power of item is enough and the difficulty of item in middle categorized. This result shows that the instrument of mathematical communication test that has been developed valid and reliable. So, the instrument can be used as an instrument of data collection research.